2018
DOI: 10.1259/bjr.20170959
|View full text |Cite
|
Sign up to set email alerts
|

Liver fat imaging—a clinical overview of ultrasound, CT, and MR imaging

Abstract: Hepatic steatosis is a frequently encountered imaging finding that may indicate chronic liver disease, the most common of which is non-alcoholic fatty liver disease. Non-alcoholic fatty liver disease is implicated in the development of systemic diseases and its progressive phenotype, non-alcoholic steatohepatitis, leads to increased liver-specific morbidity and mortality. With the rising obesity epidemic and advent of novel therapeutics aimed at altering metabolism, there is a growing need to quantify and moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
185
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(195 citation statements)
references
References 87 publications
4
185
1
5
Order By: Relevance
“…The degree of steatosis in our study cohort was significantly correlated with the presence of NASH. This may be clinically significant, as steatosis can be evaluated using magnetic resonance imaging–estimated proton density fat fraction (PDFF) . A recent study in adults with NASH found that PDFF correlates well with histologic hepatic steatosis grade .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The degree of steatosis in our study cohort was significantly correlated with the presence of NASH. This may be clinically significant, as steatosis can be evaluated using magnetic resonance imaging–estimated proton density fat fraction (PDFF) . A recent study in adults with NASH found that PDFF correlates well with histologic hepatic steatosis grade .…”
Section: Discussionmentioning
confidence: 64%
“…This may be clinically significant, as steatosis can be evaluated using magnetic resonance imaging-estimated proton density fat fraction (PDFF). 16 A recent study in adults with NASH found that PDFF correlates well with histologic hepatic steatosis grade. 17 If steatosis degree in children is indeed correlated with the presence of NASH, and if steatosis can be estimated using non-invasive PDFF, this may eventually negate the need for invasive liver biopsies in some patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, liver biopsy cannot be performed in all patients, as it is an expensive and invasive procedure which limits its use for the screening of population (6). Thus, several studies developed noninvasive imaging techniques such as ultrasonography, computerized tomography (CT) and MRI to clinically assess HS in NAFLD (7,8). However, ultrasonography is observer dependent, CT induces radiation exposure, and MRI is not routinely accessible.…”
Section: Introductionmentioning
confidence: 99%
“…However, liver biopsy is an invasive procedure with a non-negligible risk of significant morbidity and mortality. MRI is the most sensitive and specific noninvasive technique for assessing hepatic steatosis [18] and may be better for detecting the development or progression of NAFLD after ADT. Progression of NAFLD was identified after 6 months of ADT in patients with PCa and was strongly correlated with changes in HbA 1c , abdominal circumference, and BMI.…”
Section: Impact Of Adt On Nafld Progression Inmentioning
confidence: 99%